If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3ax + -2 = 5bx + 7 Reorder the terms: -2 + 3ax = 5bx + 7 Reorder the terms: -2 + 3ax = 7 + 5bx Solving -2 + 3ax = 7 + 5bx Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3ax = 7 + 2 + 5bx Combine like terms: -2 + 2 = 0 0 + 3ax = 7 + 2 + 5bx 3ax = 7 + 2 + 5bx Combine like terms: 7 + 2 = 9 3ax = 9 + 5bx Divide each side by '3x'. a = 3x-1 + 1.666666667b Simplifying a = 3x-1 + 1.666666667b Reorder the terms: a = 1.666666667b + 3x-1
| 10x+4+3+6=7x+3+6x | | 7(x+9)=4[x-(6-x)] | | 3(x-3)+16=2(x+5) | | 6x+6= | | 10x+2+4x+7=13x+3 | | 12y-9=16y+19 | | 9x-3=3+8x | | 7x+3y=16 | | 23-6x=-61 | | v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p |